A reutilização de seringas e agulhas descartáveis na aplicação de insulina: estudo em um serviço de referência localizado em São Luiz-MA - Fortes, Maria Líbia Marques (2003)
This work is about a descritive - exploratory study whose objective is to know the procedures related with the re-using of rejected syringes and needles, in the aplication of insulin dose. It was participating of the sample, 215 diabetes millitus carrier, all of then trated in Dutra President Unity of University Hospital, in São Luís, Maranhão, during May to October of 2002. the data collect happened using methodology resources, for example: structured interview and directed observation. Data were analysed using as base the adequate literature, the orientations that the clients got in the Service and, after, codifyied and processed by a Data Bank of EPI - INFO Program, version 2000. T-students and qui-quadrado tests were used to verify the association between adopted procedures and the changing and the accidents, and for “p” lesser than or equal to 0,05, it was considered the association estatisticly significative. The resuíts made evident that most of examined persons re-use the syringes and needles about seven times, what is in accordance with the literature. However, there is a percentual that is making mistakes, like these: breathe in alcohol to “wash” the syringe (5,1%); use cotton with alcohol to “clean” the needle (23,7%); “wash” the syringe and needle with water and soap (2,8%); boil the syringes and needles (4,2%); keep the syringes and needles contesting the principies of re-using (53,0%); re-use syringes and needles of another diabetes carrier (2,8%) re-use syringes and needles when they were contamined during re-using process (9,3%); when the needle was rhombed (4,7%) and when it was curved (2,3%); don’t wash the hands to execute the technical of insulin administration (28,4%); don’t make the desinfection of the rubber lid from the blttle (65,6%) and don’t make the anti-sepsis in the aplication places (7,4%). It’s important to say that 34,9% of diabetes carrier had changes in the places of insulin application and 35,8% had accidents with the needle. About the associations, they were significative to the keeping of ejected syringes and needles, to the procedure adopted when the syringes and needles touch any object and to the procedures about the cleaning of the place to applicate the insulin dose. Taking these resuíts as base, it’s possible to deduce that a parcel of the studied sample isn’t understanding the orientations received in the health Services about the re-using of rejected syringes and needles principies of the insulin administration, showing that the multidiscipline group must to search the ways to solve the matter. Key-words: mellitus diabetes; insulin; re-using of rejected syringes and needles.